Low-frequency signals support perceptual organization of implant-simulated speech for adults and children. (April 2014) - Nittrouer, Susan; Tarr, Eric; Bolster, Virginia; Caldwell-Tarr, Amanda; Moberly, Aaron C.; Lowenstein, Joanna H.
Abstract Objective: Using signals processed to simulate speech received through cochlear implants and low-frequency extended hearing aids, this study examined the proposal that low-frequency signals facilitate the perceptual organization of broader, spectrally degraded signals. Design: In two experiments, words and sentences were presented in diotic and dichotic configurations as four-channel noise-vocoded signals (VOC-only), and as those signals combined with the acoustic signal below 0.25 kHz (LOW-plus). Dependent measures were percent correct recognition, and the difference between scores for the two processing conditions given as proportions of recognition scores for VOC-only. The influence of linguistic context was also examined. Study sample: Participants had normal hearing. In all, 40 adults, 40 seven-year-olds, and 20 five-year-olds participated. Results: Participants of all ages showed benefits of adding the low-frequency signal. The effect was greater for sentences than words, but no effect of diotic versus dichotic presentation was found. The influence of linguistic context was similar across age groups, and did not contribute to the low-frequency effect. Listeners who had poorer VOC-only scores showed greater low-frequency effects. Conclusion: The benefit of adding a low-frequency signal to a broader, spectrally degraded signal derives in some part from its facilitative influence on perceptual organization of the sensory input.